Elite dan Integrasi Sosial dalam Masyarakat Pagersari, Mungkid, Magelang 1967-1988 - Tri Karyanti (Department of History, Faculty of Humanities, Diponegoro University, 2018)
This study examines the significant role of local elites in the efforts of social integration in Pagersari, Mungkid, Magelang. Social integration is the cooperation of all society members, ranging from individuals, families, and society, so it can generate unity and diversity in the form of shared values. In the realization of social integration, it required leaders who were able to integrate all kind of conflicts in society. After 30 September 1965 event until the reign of the New Order in Pagersari, there were various internal conflicts among people who were motivated by various problems such as political differences, religious and family internal affairs. It is known that the active role of local leaders or elites has especially become an important factor to solve these conflicts. It even able to encourage the realization of social integration in Pagersari. To handle conflicts, it was solved by finding the core problems, then trying to resolve until accepted by the conflict’s parties. Some of the media for integration by a good leadership, religious and cultural approach.